2015
DOI: 10.1002/jcp.25033
|View full text |Cite
|
Sign up to set email alerts
|

Stable Incretin Mimetics Counter Rapid Deterioration of Bone Quality in Type 1 Diabetes Mellitus

Abstract: Type 1 diabetes mellitus is associated with a high risk for bone fractures. Although bone mass is reduced, bone quality is also dramatically altered in this disorder. However, recent evidences suggest a beneficial effect of the glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide 1 (GLP-1) pathways on bone quality. The aims of the present study were to conduct a comprehensive investigation of bone strength at the organ and tissue level; and to ascertain whether enzyme resistant GIP or G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 53 publications
(63 reference statements)
7
49
0
Order By: Relevance
“…In the present study, although both STZ and OVX led to bone loss in rats, their action mechanisms are apparently different. In the diabetic rats, serum OC and osteoblast count were markedly reduced, and these observations are consistent with previous reports (13,26). In the meanwhile, serum CTX-1 and osteoclast count were only slightly increased in STZ-induced diabetes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the present study, although both STZ and OVX led to bone loss in rats, their action mechanisms are apparently different. In the diabetic rats, serum OC and osteoblast count were markedly reduced, and these observations are consistent with previous reports (13,26). In the meanwhile, serum CTX-1 and osteoclast count were only slightly increased in STZ-induced diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…Since expression of functional GLP-1 receptors was identified on osteoblasts (23), the potential beneficial effects of GLP-1 RAs has been evaluated experimentally on diabetic and non-diabetic models (11,13,15,16,24,25). Previous studies have demonstrated that liraglutide treatment could increase BMD, improve bone micro-architecture and restore mechanical properties of the bone in diabetic rodents (13,14), and it also exerts beneficial effects on the bone in non-diabetic osteoporotic models (15,16). In the present study, we constructed a rat model of osteoporosis induced by both diabetes and OVX, and showed that long-term liraglutide treatment was able to ameliorate the defects in the bone of the severely osteoporotic rats.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent data suggest that incretins could also have a positive effect on bone quality in T1DM. In streptozotocin-treated mice, incretin peptides were able to prevent the alterations of cortical microarchitecture and the deterioration of bone quality (99). Clinical studies are needed to determine if the rodent data is applicable and to elucidate the effects of incretin on fracture risk.…”
Section: Insulin Incretin and Igf1mentioning
confidence: 99%
“…It was found that GLP-1 could reduce these trends and restore normal bone structure (17). In streptozotocin-induced T1DM Swiss TO mice, liraglutide improved mechanical properties in bone tissue, but failed to reverse cortical microstructure degradation or improve whole bone mechanical properties (18). Furthermore, GLP-1 and glucose-dependent insulinotropic polypeptide double incretin receptor knockout (DIRKO) mice had increased trabecular bone mass and a higher trabecular number compared to wild-type mice, with reduced bone outer diameter, cortical thickness, and cortical area.…”
Section: The Impact Of Glp-1 On Bone Metabolismmentioning
confidence: 99%